Filgotinib (GLPG0634/GS-6034), an oral selective JAK1 inhibitor, is effective as monotherapy in patients with active rheumatoid arthritis: results from a randomised, dose-finding study (DARWIN 2). Issue 6 (19th December 2016) - Kavanaugh, A; Kremer, J; Ponce, L; Cseuz, R; Reshetko, O V; Stanislavchuk, M; Greenwald, M; Van der Aa, A; Vanhoutte, F; Tasset, C; Harrison, P
Abstract : Objectives: To evaluate the efficacy and safety of different doses of filgotinib, an oral Janus kinase 1 inhibitor, as monotherapy in patients with active rheumatoid arthritis (RA) and previous inadequate response to methotrexate (MTX). Methods: In this 24-week phase IIb study, patients with moderately to severely active RA were randomised (1:1:1:1) to receive 50, 100 or 200 mg filgotinib once daily, or placebo, after a ≥4-week washout from MTX. The primary end point was the percentage of patients achieving an American College of Rheumatology (ACR)20 response at week 12. Results: Overall, 283 patients were randomised and treated. At week 12, significantly more patients receiving filgotinib at any dose achieved ACR20 responses versus placebo (≥65% vs 29%, p<0.001). For other key end points at week 12 (ACR50, ACR70, ACR-N, Disease Activity Score based on 28 joints and C reactive protein, Clinical Disease Activity Index, Simplified Disease Activity Index and Health Assessment Questionnaire-Disability Index) significant differences from baseline in favour of filgotinib 100 and 200 mg versus placebo were seen; responses were maintained or improved through week 24. Rapid onset of action was observed for most efficacy end points. Dose-dependent increases in haemoglobin were observed. The percentage of patients with treatment-emergent adverse events (TEAE) was similar in the placebo and filgotinib groups (∼40%). Eight patients on filgotinib and one on placebo had a serious TEAE, and four patients, all of whom received filgotinib, experienced a serious infection. No tuberculosis or opportunistic infections were reported. Conclusions: Over 24 weeks, filgotinib as monotherapy was efficacious in treating the signs and symptoms of active RA, with a rapid onset of action. Filgotinib was generally well tolerated. Trial registration number: NCT01894516 .